Delayed anticoagulation proteins recovery in severe thalassemia diseases compared to malignancies in children after hematopoietic stem cell transplantation - Nongnuch Sirachainan (2022)
Alterations of hemostasis have been observed following hematopoietic stem cell transplantation (HSCT). In thalassemia diseases, the evidences of coagulation stimulation have been observed in patients with thalassemia major with and without splenectomy. The comparison between thalassemia disease before and after HSCT, and malignancy has never been reported. The hemostasis parameters in 8 patients with thalassemia disease and 10 patients with malignancy before, day 0, days 14, days 30, days 60, days 90, and days 180 of HSCT were studied. The median (range) ages in thalassemia, malignancy and normal control groups were 8.5 (2 to 17), 11.0 (2.0 to 19.0) and 10.0 (0 to 16.0) years, respectively (p=0.42). D-dimer level was significantly higher during days 14 to 60 of HSCT in both groups when compared to the normal control group. Protein C and antithrombin activities were significantly lower during HSCT in thalassemia when compared to the malignancy and normal control groups, while, no changes of anticoagulation proteins in malignancy group were observed.